Human amygdala nuclei show distinct developmental trajectories from adolescence to adulthood in functional integration with prefrontal circuitry - Ojha, Amar; Foran, Will; Calabro, Finnegan J.; Sydnor, Valerie J.; Petrie, Daniel J.; Parr, Ashley C.; Famalette, Alyssa; Phang, Natalie; Sista, Arshia; Sorrells, Shawn F.; Luna, Beatriz (Cell reports (Cambridge), 2025)
Adolescent neurodevelopment of affective and cognitive control, crucial for healthy functioning and impaired transdiagnostically, is supported by refinements between the amygdala and prefrontal cortex (PFC). Due to technical limitations, fronto-amygdala connectivity remains poorly characterized. Here, we leverage multimodal longitudinal 7 T neuroimaging data in 143 healthy participants aged 10–32 to examine developmental trajectories between subject-specific amygdala nuclei and PFC subregions. We find age-related functional connectivity changes between the lateral PFC and basolateral amygdala, ventral portions of the PFC and central amygdala, and the anterior cingulate cortex and corticoamygdaloid transition area. Variability in connectivity strength relates to individual differences in affective and cognitive control. Using a data-driven meta-analytic decoding approach, we find functional specialization across nuclei and development. Together, these data recapitulate amygdala heterogeneity from animal models and inform how diverse subcircuits support adaptive functioning and confer psychiatric risk during developmental windows of heightened plasticity. [Display omitted] •Ultra-high-field 7 T fMRI was used to segment amygdala nuclei•Fronto-amygdala functional connections develop along distinct trajectories•Age-related connections relate to affective and cognitive control•Amygdala nuclei exhibit developmental and functional specialization Ojha et al. use longitudinal 7 T neuroimaging to characterize distinct developmental trajectories of fronto-amygdala connectivity across nuclei through adolescence. They identify how age-related connections support affective and cognitive control and find amygdala nuclei to exhibit functional and developmental specialization.